MODEL PENELITIAN BUKU IBN AL-'ARABI WAHDAT AL-WUJUD DALAM PERDEBATAN - Ghofir, Abd (Kopertais Wilayah X Jawa Tengah, 2017)
One form of discipline and moral responsibility of a scholar, when writing a dissertation is the fulfillment of the demands of a new discovery according to the field of the scratch. Likewise, of course, a dissertation written by Dr. Kautsar Azhari Noer entitled